INNOVATIVE TRANSFORMATIONS OF ROAD TRANSPORT ENTERPRISES IN CONDITIONS OF UNCERTAINTY - GALYTSKYI, Bogdan; SPITSYNA, Anhelina (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article identifies the importance of innovation processes in the development of transport services. The main trends affecting the development of the transport industry are considered. The need for innovative development of motor transport enterprises in modern conditions of uncertainty is raised. The factors limiting the innovation process of the transport industry are identified. The main challenges of innovative transformations of motor transport enterprises are investigated. The directions of activating innovative development in the transport industry are identified, in particular, digital technologies in the transport sector are presented. Key innovative tools for the transformation of motor transport enterprises are presented. A positive result and successful activity of enterprises largely depend on its ability to innovate - an activity aimed at using and commercializing the results of scientific research and development and leading to the release of new competitive goods and services to the market. New trends in the development of transport and increasing safety demonstrate a significant technological breakthrough aimed at creating a sustainable future, optimizing traffic and protecting citizens. The digitalization of transport concerns not only the connection of cars to the Internet, but also the general integration of transport systems into single digital platforms. Modern cars can receive real-time information about traffic, weather, accidents and other factors affecting traffic thanks to Vehicle-to-Everything systems. This technology allows cars to interact with infrastructure, other vehicles and even pedestrians. It has been analyzed that rapid unpredictable changes affect the performance of a motor transport enterprise, while at the same time, to some extent, devaluing the effective value of existing classical approaches to management. Instead, new technologies are emerging that radically change management techniques, tools and means of influence. According to the results of the study, it was found that the use of the latest advanced technologies has great potential for the development and improvement of the management of motor transport enterprises. The results of the study indicate the validity of the use of innovative technologies to increase and improve the economic potential of the transport industry.